E-LKPD BERBASIS ETNOMATEMATIKA JEMBATAN BRAWIJAYA UNTUK MENINGKATKAN KETERAMPILAN PEMECAHAN MASALAH GEOMETRI SISWA SMK - Ruly Eka Putri, Anggila; Rihatul Hima, Lina; Santia, Ika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop an E-LKPD based on the Brawijaya Bridge ethnomathematics model that meets the criteria of validity, practicality, and effectiveness in improving the geometric problem-solving skills of 10th-grade students at SMKN 1 Semen. The study employed the Research and Development (R&D) method using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The product was pilot-tested on 32 10th-grade students at SMKN 1 Semen as research subjects. Before implementation, the E-LKPD was first validated by subject matter experts, media experts, and practitioners to determine the product’s suitability. The research instruments included a validation sheet, a student response questionnaire, and pretests and posttests to measure students’ geometric problem-solving skills. The data were analyzed using percentages to determine the validity and practicality of the product, while effectiveness was analyzed using the Shapiro-Wilk normality test and the Paired Sample t-test. The validation results show that the E-LKPD has a very good level of suitability, with approval rates of 81% from subject matter experts, 96% from media experts, and 88.18% from practitioners. Student responses to the use of E-LKPD achieved an average percentage of 77.06%, which falls into the “good” category. The pretest and posttest results showed an increase in the average student score from 79.88 to 93.28, representing a 16.77% increase. Furthermore, the results of the Paired Sample t-Test yielded a Sig. (2-tailed) value of 0.000 < 0.05, indicating a significant difference between the pretest and posttest results. Thus, the Jembatan Brawijaya ethnomathematics-based E-LKPD is deemed valid, practical, and effective in improving students’ geometry problem-solving skills.